Potential Climate-Driven Impacts on the Distribution of Generalist Treefrogs in South America - Vasconcelos, Tiago S. [UNESP]; Do Nascimento, Bruno T. M. [UNESP] (Herpetologists League, 2016)
Climate change is considered a serious threat to biodiversity. If populations no longer have physiological, morphological, or behavioral adaptations to withstand novel climatic conditions, or if they are unable to change the timing of crucial life-history events to avoid the months with unfavorable climates, the only alternative might be to track appropriate conditions in space and follow them. This study explores the latter scenario and evaluates the potential spatial effects that climate change might exert on four wide-ranging generalist anurans from South America. Using six methods to model ecological niches and different climate change scenarios for 2050, we found that these treefrog species are predicted to experience a contraction in their geographical ranges at magnitudes varying from 13.90% (Dendropsophus nanus) to 52.06% (D. minutus) because of the loss of climatically suitable areas. These areas are mainly located in the northern perimeter of the current species distribution. Conversely, only minor gains in new climatically suitable areas are predicted for these species (except for D. minutus). Finally, all species are predicted to be found almost exclusively within the Brazilian Atlantic Forest and to be absent from the lowlands of the Pantanal floodplains by 2050.
Keywords: Anura; Biogeography; Ecological niche modeling; Ensemble forecast; Hylidae